(untitled) (Numerus academy review, 2026)
The development and expansion of de administrative function have led to the emergence of a system administrative delegation,that is considered procedure exceptional for the principle of jurisdication,it requires the transfer of part of the president powers managing to this subordinate based on a legal text that it is authorized and subject to legal controls distinguish it from some legal systems that are similar to it on the other hand, to be a project and a prize from legal.